Effect of rapid cryopreservation on meiotic recombination in human spermatocytes. Issue 10 (18th July 2016) - Song, Wenyan; Zhao, Wanli; Yang, Qinglin; Wang, Xuegai; Jin, Haixia; Yao, Guidong; Peng, Zhaofeng; Shi, Senlin; Yang, Hongyi; Sun, Yingpu
Abstract: Objective: To evaluate the safety of rapid cryopreservation for human testicular tissues by comparing the meiotic recombination in the fresh and thawed testis after rapid freezing. Methods: Twelve male patients with prostate cancer (PC) who had given birth to healthy children at youth and need to receive surgical removal of testicular tissue at present were selected in this study. Testicular tissues from 4 cases of PC patients were randomly divided into two parts, one part as fresh tissue and the other to receive rapid freezing treatment. Fidelity analysis for homologous genetic recombination and synapsis were performed by immunofluorescence after prepared by a micro‐spreading technique. Results: The average number of MLH1 foci per cell, autosomal synaptonemal complex (SC) containing 0∼5 MLH1 foci and percent of cells with one MLH1 focus on XY chromosome showed no difference between the fresh and frozen thawed testicular tissues from the same case ( P >0.05). And, no significant difference in the frequency of gaps and splits on SCs was observed in fresh and thawed spermatocytes ( P > 0.05). Conclusion: Rapid cryopreservation showed little effect on the frequency of meiotic recombination and fidelity of synapsis in human spermatocytes from PC patients, and acted as an effective method for preserving male fertility.